PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA KARTU GAMBAR PADA KELOMPOK B TK HOLY FAITHFUL OBEDIENT DEPOK - Puji Yulianty; Emma Veviana R (Jurnal Anak Bangsa, 2022)
This study aims to improve early reading skills through picture cards in group B at Holy Faithful Obedient Kindergarten, Depok. This research is motivated by the lack of early reading ability of children in group B2 (aged 5-6 years). This research is a classroom action research conducted collaboratively using the Kemmis and Mc. Taggart, which is performed for two cycles. The subjects of this study were children in group B2 at Holy Faithful Obedient Kindergarten, totaling 15 children, consisting of 8 boys and 7 girls. The object of this research is the ability to read the beginning using picture cards. The method used in collecting observational data, while the data analysis technique was used qualitatively and quantitatively. The indicators studied are indicators that state the sound symbols of letters, differences in letters, mention objects/words that have initial letters, and connect words with symbols/symbols. The results showed that picture cards could improve the early reading ability of group B in Holy Faithful Obedient Kindergarten. This can be seen from the significant increase in initial reading ability. This increase can be seen from the results of observations at the end of the improvement of the initial reading ability development activity using picture word cards as media